Increase in the Number of IBD Surgical Resections at the Puerto Rico Medical Center: A Brief Report - González-Keelan Md, Carmen; Arce, Vicmarie; Ortiz, Ana P.; Torres, Esther A.; Lojo, Juan J. (Puerto Rico Health Sciences Journal, 2012)
Objective: There is limited data describing Inflammatory Bowel Disease (IBD) among Hispanics. In Puerto Rico, three studies have been conducted that estimate the prevalence of this disease. Although still rare, these studies coincide that IBD has increased during the last decades. This study aims to describe the IBD surgical resections received in the Pathology Laboratory of the Puerto Rico Medical Center (PRMC) in two periods: 1966-82 and 2002-2008. Methods: A retrospective review of the Surgical Pathology reports was done. A total of 133 reports complied with the inclusion criteria for IBD out of a total of 314,493 pathologies evaluated. For purposes of comparison, the data was grouped into 3 time periods: 1966-1973, 1974-1982 and 2002-08. Results: The number of IBD cases per 100,000 pathologies for the period 1966-73 was 15.1, for the period 1974-82 was 19.1 and for the period 2002-08 was 125.0. The number of IBD resections increased 87.9% when comparing years 1966-73 with 2002-2008, with similar increases in Ulcerative Colitis and Crohn’s Disease. Although this result was not statistically significant (p > 0.05), a higher proportion of IBD patients had an IBD resection at a younger age in the 2002-2008 time period. A change in the sex profile of the patients was also identified; the majority of cases (75%) were females in the years 1966-1973 while 50.6% were males in 2002-2008. Conclusion: Our results confirm an increase in IBD surgical resections at the PRMC. Although not significant, a higher proportion of incident cases are occurring among younger age groups and the distribution of incident cases has become similar between males and females in recent years.